The Contribution of Interdisciplinarity to the Development of Competencies for WorkRelated Mental Health in Primary Health Care - Alexandrino, Leonardo; Bianco, Mônica de Fatima; Moraes, Thiago Drumond; Alves, Roberta Belizário (Organizações & Sociedade, 2024)
This study aimed to investigate the process of developing competencies for working with WorkRelated Mental Health (WRMH) in primary health care. The research is anchored on a referential that discusses the notion of competencies and their development in a contextualized way, stemming from the interpretivist paradigm. Additionally, it resorts to discussions about interdisciplinarity, social determinants of health processes, and WRMH in primary care. The research has a qualitative approach. The data were produced through semi-structured interviews, which were recorded, transcribed, and subjected to thematic content analysis, with a posteriori categorization. The results show little inclusion of WRMH in primary care, a lack of integration between sectors and professionals and the existence of some actions developed in an interdisciplinary way. The competency development strategies foster interdisciplinarity but do not adequately address the mental health of workers who use the services. This study provides an in depth look at the relationships between interdisciplinarity and competency development in WRMH. It is concluded that interdisciplinarity contributes to the development of competencies, while at the same time it is an important competence for performance in primary care. The concept of competence linked to the professional category, the influence of disciplinary training, and the scarcity of resources limit the use of interdisciplinarity in the development of competencies, especially regarding WRMH, which is considered the responsibility of specialized areas.